INSTITUTIONAL MODELLING OF THE MANAGEMENT SYSTEM FOR REGIONAL PARTICIPANTS OF DUAL EDUCATION - A. Yu. Kokovikhin; A. G. Mokronosov; E. S. Ogorodnikova (Obrazovanie i Nauka)
Introduction. The need for increasing the investment attractiveness of Russian regions and meeting the needs of territories for qualified personnel updates the search for infrastructure and coordination mechanisms and tools of the solution of these problems. At the same time, the diversity of interests of participants in dual education and their various structural positions do not allow to solve this task by directive methods, both on the part of state structures and corporate sectors. One of the solutions might be to form an effective management system for dual education, which assumes the organisation of practical vocational training according to inquiries of employers, who are involved in implementation of educational process in order to promote labour market with in-demand experts. The aim of the present research was the scientific substantiation of the choice of the institutional model for management of dual education system at the regional level, taking into account the interests of all its members: enterprises, government agencies, students and educational institutions.Methodology and research methods. The research was based on the systematic approach. The methods of modelling and comparative analysis were employed. The provisions and principles of utility theory served as the methodological basis of institutional model formation.Results and scientific novelty. The main target reference points of regional participants of dual education were identified and formalised in the form of certain indicators. Two types of models of management of these subjects were considered: models with and without the usage of institutional superstructures. As a key criterion for model selection, maximization of a complex indicator of its utility for interested parties was offered. In particular, it was demonstrated that supervision of graduates by a certain employer is caused by parameters of employment attractiveness, such as a wide range of horizontal and vertical career cards and a possibility of continuing vocational education. The conducted quantitative research on utility indicators allowed the authors to design the institutional model for management of regional participants within the system of dual education and to recommend it for further implementation.Practical significance. The institutional model presented in the publication is directed to the solution of tasks faced by partner companies and educational establishments within the system of dual education. When applying this model, it is possible to forecast personnel requirements – job availability in the future of jobs, resulting to a considerable simplification of vocational guidance  work, which can be carried out in the course of applicants’ preparation.